Obstáculos y mejoras de un profesor universitario de ciencia para conseguir una participación argumentativa de sus estudiantes - Briceño-Martínez, John Jairo (Revista Científica, 2017)
Research results of a formative investigation process of twelve hours are shown in this paper. The main purpose of this investigation is to guide and walk a university professor (AXL) to design and implement activities that promote argumentative participation of his students throughout a process that is called supervision. This research is a case study based on three nonparticipating observations, in which it is investigated the effect and impact that teachers’ participation in argumentative talks have in students. It is concluded that AXL learned how to drive students into the argumentative process and promoted participation in the classroom; however, despite the effort of the teacher, his/her students neither reached nor achieved the expected argumentative level in spite of their participation.